The influence of range hood exhaust orientation on capture efficiency. (3rd July 2021) - Meleika, Sammy; Pate, Michael
Abstract : In this study a test procedure for determining capture efficiency (CE) of domestic range hoods, namely ASTM-E3087.18, was used to investigate how changing the exhaust orientation of residential range hoods influences CE. Previous studies on residential range hood CE only utilized vertical discharge orientation and do not strictly adhere to ASTM-E3087.18. Furthermore, many range hoods are installed in households using horizontal discharge. In the study reported herein, testing was performed on five range hoods of similar design using both vertical and horizontal exhaust orientations and at a fixed mounting height. Resulting CE values ranged from 50.9 to 94.1%CE with CE varying by as much as 10.6%CE and uncertainty (δ) varying less than 1.0%CE when changing discharge orientation for a specific case. No consistent trend was observed among all range hoods when changing from vertical to horizontal orientation with 30% of cases showing an increase in CE, 30% showing a decrease and 40% showing no change. Exhaust orientation was found not to have a significant influence on CE uncertainty, but had varying effects on repeatability, reproducibility and variability. Additionally, inconsistent exhaust duct design, which may lead to the development of "CO2 Pockets, " can result in worsened variability performance when comparing exhaust orientations.